MAGANG WIRAUSAHA SEBAGAI MEDIA PEMBERDAYAAN MAHASISWA STP ST. PETRUS KEUSKUPAN ATAMBUA DALAM PERSPEKTIF ENSIKLIK LABOREM EXERCENS PAUS YOHANES PAULUS II - Manek, Agnes Prisilia; Siri, Theodorus Asa (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2023)
"Work and pray". Working without trust through prayer to Allah the Creator is futile. Work is a fundamental and significant aspect that reflects human nature in life as a mission in the world as stated in the encyclical Laborem Exercens. This paper aims to explore the meaning of work in an entrepreneurial internship from the perspective of the encyclical Laborem Exercens so that it can be the right medium for developing students' abilities, skills and creativity in carrying out entrepreneurial internships. The contents of the encyclical Laborem Exercens explain in depth the meaning of work as a work of service to God. So it is very important for students to understand the meaning of work through entrepreneurial internships in order to fulfill their duties and mission in the world.